Employment effects of privatisation and foreign acquisition of Chinese state-owned enterprises - Yundan Gong; Holger Görg; Sara Maioli (Institute for the Study of Labor (IZA), 2006)
This paper investigates the effects of domestic privatisation or foreign acquisition of Chinese State Owned Enterprises (SOEs) on employment growth, using firm level data for China and a combination of propensity score matching and difference-in-differences in order to identify the causal effect. Our results suggest that, controlling for output growth there is some evidence that domestic privatisation leads to contemporaneous reductions in employment growth compared to firms that did not undergo an ownership change. By contrast, there is some evidence that foreign acquisitions show higher employment growth in the post acquisition period than non-acquired SOEs.
Keywords: 330; Privatisierung; Sozialistisches Unternehmen; Multinationales Unternehmen; Direktinvestition; Beschäftigungseffekt; China